2017
DOI: 10.1177/0884533617712488
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Support for Critically Ill Patients With Cancer

Abstract: Oncology patients often experience the classic signs of malnutrition-weight loss as well as fat and muscle wasting, which have been associated with poor tolerance to treatment and increased morbidity and mortality. Nutrition status may be an important factor in determining tolerance to treatment and outcomes associated with it. Thus, identification of those with preexisting malnutrition or who are at risk for developing malnutrition is crucial not only at time of cancer diagnosis but also throughout the treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 81 publications
0
9
0
1
Order By: Relevance
“…23 Malnutrition, reflected by hypoalbuminemia, is associated with increased morbidity and mortality. 24 Several studies have shown that malnutrition also interferes with the patient’s response to cancer treatment, 25 and malnutrition is related to immunosuppression, which provides a favourable microenvironment for tumour recurrence. 26 , 27 The association between inflammation and tumours was first noticed by Virchow in 1863.…”
Section: Discussionmentioning
confidence: 99%
“…23 Malnutrition, reflected by hypoalbuminemia, is associated with increased morbidity and mortality. 24 Several studies have shown that malnutrition also interferes with the patient’s response to cancer treatment, 25 and malnutrition is related to immunosuppression, which provides a favourable microenvironment for tumour recurrence. 26 , 27 The association between inflammation and tumours was first noticed by Virchow in 1863.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the consumption and invasion of tumour diseases and the injuries brought by various treatment procedures, cancer patients often have a process of fat and muscle consumption and weight loss, resulting in malnutrition, low immunity, poor tolerance to treatment and high mortality. (5,6) Clinical studies have preliminarily shown that omega-3 fatty acids can improve the prognosis of critically ill patients (7,8). In addition, the fatty acids can also improve the inflammatory responses and nutritional status of malignant tumour patients, enhance their immune function and the sensitivity and tolerance to tumour radiotherapy and chemotherapy, and inhibit tumour growth.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that numerous metabolic disorders and negative energy balance in malignancies lead to malnutrition and cachexia. 35,36 According to the results of other studies, the prevalence of hospital malnutrition is high in oncology patients. 22,37,38 Pirlih pointed to malignancy as one of three independent predictors of malnutrition on hospital admission.…”
Section: Risk Factors For Malnutritionon During Hospitalizationmentioning
confidence: 99%